2009
DOI: 10.1175/2009jpo4190.1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Thermohaline Intrusions in the North Pacific Subtropical Frontal Zone

Abstract: A monthlong field survey in July 2007, focused on the North Pacific subtropical frontal zone (STFZ) near 308N, 1588W, combined towed depth-cycling conductivity-temperature-depth (CTD) profiling with shipboard current observations. Measurements were used to investigate the distribution and structure of thermohaline intrusions. The study revealed that local extrema of vertical salinity profiles, often used as intrusion indicators, were only a subset of a wider class of distortions in thermohaline fields due to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 40 publications
6
53
0
Order By: Relevance
“…We note, however, that horizontal mixing associated with small-scale frontal dynamics may also be important for mixing and transport in the region. In a study of the North Pacific STFZ, it was shown that interleaving across a frontal zone was very intense within a distance of about 5 km from the front (Shcherbina et al 2009). Such smallscale features were not resolved by the station spacing in this study, but such mixing processes may further enhance vertical nutrient fluxes.…”
Section: Vertical Nutrient Fluxes In the Frontal Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note, however, that horizontal mixing associated with small-scale frontal dynamics may also be important for mixing and transport in the region. In a study of the North Pacific STFZ, it was shown that interleaving across a frontal zone was very intense within a distance of about 5 km from the front (Shcherbina et al 2009). Such smallscale features were not resolved by the station spacing in this study, but such mixing processes may further enhance vertical nutrient fluxes.…”
Section: Vertical Nutrient Fluxes In the Frontal Regionmentioning
confidence: 99%
“…The countercurrent in the gyres has been found to be associated with interactions between general wind-driven circulation (from the Westerlies and trades), thermal stratification (Cushman-Roisin 1984), and mixed layer depth distribution (Kubokawa & Inui 1999) of the upper ocean. High-resolution studies of the small-scale fron tal structures in the Northern Pacific STCZ revealed intense mixing and interleaving on spatial scales of ~5 km in the upper 150 m of the water column (Shcherbina et al 2009). The STCZ is therefore a consistent feature of the subtropical gyres.…”
Section: Introductionmentioning
confidence: 99%
“…This might not be the case in summer when solar heating warms the seasurface on both sides the front. Shcherbina et al (2009) show that a front they mapped in July could be detected in MODIS imagery of SST (Figure 18.15). The SST image, however, poorly defines the extent of the front.…”
Section: Discussionmentioning
confidence: 92%
“…4: 77.5Hz PSK Test from Q1 to ODVLA 132 Figure 15.5: 77.5Hz MSK Test from Q1 to ODVLA 133 Figure 15.6: 25.575Hz PSK Test from Q1 to ODVLA 134 Figure 15.7: 25.575Hz MSK Test from Q1 to ODVLA 135 Figure 15.8: 19.375Hz PSK Test from Q1 to ODVLA 136 Figure 15.9: 19.375Hz 146 Figure 16.6: 19.375Hz Transmission from Q46 to ODVLA 147 Figure 16.7: 77.5Hz Transmission from Q46 to ODVLA 148 Figure 17.1: Map shows location of Knudsen seismic profiles shown in Shcherbina et al (2009) 192 Figure 18.16: Section along 158°W during July 6, 2007193 Figure 18.17: Profiles of salinity and temperature in 2008near MV1308 194 Figure 18.18: map of CTD transects used used to study fronts 195 Figure 18.19: section along 137°30'W in June 1972196 Figure 18.20: section along 137°30'W in June 1973197 Figure 18.21: section along 137°30'W in June 1974 …”
Section: Index Of Figuresmentioning
confidence: 99%
“…Vertical profiles of temperature and salinity are often characterized by zigzag pattern and different inversion which is a sign of thermohaline intrusion. It is also observed as recognizable interleaving in temperature and salinity diagrams [9] [10] [11] [12]. [13] showed that on average, the slope of thermohaline intrusion located between isopycnal and isohaline slopes.…”
Section: Introductionmentioning
confidence: 99%